iOS user-centric design developer talks - Terpstra, Brett; Safari eBooks ([S.l.] : Addison-Wesley, 2013)
"iOS User-Centric Design LiveLessons--Developer Talks provides you with practical advice and principles for how to strategize the design of your iOS application. iOS developer Brett Terpstra explains basic mobile design principles and demonstrates how these principles are implemented in several currently available iOS applications. This presentation does not assume any previous experience with application design."--Resource description page.
Title from title screen.
Presenter, Brett Terpstra.
Keywords: iOS (Electronic resource); Application software -- Development; iPod (Digital music player) -- Programming; iPad (Computer) -- Programming; iPhone (Smartphone) -- Programming; Mobile computing -- Programming; Electronic books